Short- and medium-term fiscal positions in a high-inflation environment: the case of Croatia (Public Sector Economics - submission site, 2023)
This paper analyses the short- and medium-term effects of high inflation on fiscal developments in Croatia. The main analytical novelty is to add inflation shocks to the fiscal reaction function, an approach that was not considered in macro-fiscal research during the long period of moderate inflation. Our results suggest that inflation has a favourable effect on the primary balance in the short term, which can be explained by the positive effect of inflation on nominal tax revenues and an initial lagged adjustment of public expenditure to inflation. In the medium term, however, inflation is likely to have a negative effect on the primary balance by raising government expenditure more than tax revenues.